2016
DOI: 10.1051/0004-6361/201527307
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of dust grains of comet 67P and connection with nucleus regions

Abstract: Aims. Multiple pairs of high-resolution images of the dust coma of comet 67P/Churyumov-Gerasimenko have been collected by OSIRIS onboard Rosetta allowing extraction and analysis of dust grain tracks. Methods. We developed a quasi automatic method to recognize and to extract dust tracks in the Osiris images providing size, FWHM and photometric data. The dust tracks characterized by a low signal-to-noise ratio were checked manually. We performed the photometric analysis of 70 dust grain tracks observed on two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Within the measurement uncertainties these values also agree with the colors and spectral gradients determined for the nucleus of 67P by Tubiana et al (2008Tubiana et al ( , 2011 and Lowry (2006). It is slightly below the spectral slope determined from in-situ measurements of dust grains in the coma of 67P (Cremonese et al 2015). No clear increase of the reddening with phase angle is seen in our data.…”
Section: Resultscontrasting
confidence: 81%
“…Within the measurement uncertainties these values also agree with the colors and spectral gradients determined for the nucleus of 67P by Tubiana et al (2008Tubiana et al ( , 2011 and Lowry (2006). It is slightly below the spectral slope determined from in-situ measurements of dust grains in the coma of 67P (Cremonese et al 2015). No clear increase of the reddening with phase angle is seen in our data.…”
Section: Resultscontrasting
confidence: 81%
“…Other examples of blue color of cometary dust can be found in Jewitt et al (1982), when comparing the high-resolution spectrum of Comet C/1980 E1 (Bowell) with the solar spectrum; the spectrum of Comet Bowell appears to be almost featureless and, therefore, Jewitt et al concluded that it is completely devoid of gaseous emission. Finally, it is worth noting the recent Rosetta measurements of the color of dust in Comet 67P/Churyumov-Gerasimenko (Cremonese et al 2016), in which 16 out of 70 individual dust grains detected in the vicinity of the nucleus have blue photometric color. Thus, the blue photometric color also can be a feature of some comets or, at least, some part of their dust.…”
Section: Introductionmentioning
confidence: 96%
“…The compact particles are correlated with lower phase angle observations (between 30° and 40°) and with the neck region of the comet, with velocities of 2.5 ± 0.8 m s −1 at 10 km from comet centre and 4.3 ± 0.9 m s −1 at 30 km [ 61 ]. Photometry of coma dust grains shows agreement with surface values, although some differences in composition from the surface could potentially indicate the presence of hydrated minerals [ 64 ]. A more detailed characterization of the dust environment was made following the collection of over 10 000 particles of scale of a few 10 µm to several 100 µm during the period 11 August 2014–3 April 2015 (3.57–1.95 AU) [ 65 ].…”
Section: Pre-landing and First Timesmentioning
confidence: 98%
“…These regions are characterized by bluer spectra, indicating ice exposure or possibly hydrated minerals [64,76], although comparisons with laboratory samples suggest this is not the case [135]. In the case of ice, erosion rates would be 1–2 orders of magnitude lower than that observed, with speculation of this enhanced erosion being driven by the low tensile strength of the surface matrix, or clathrate destabilization/amorphous ice crystallization, although observation of sulfur-bearing species in the comet have been used to argue against the existence of clathrates [136].…”
Section: Development Of Cometary Activity Comparing With Pre-perihelmentioning
confidence: 99%
See 1 more Smart Citation